(untitled) - Cengel, Yunus A. (Boston, 1997)
The text covers the basic principles of heat transfer with a broad range of engineering applications. It contains sufficient material to give instructors flexibility and to accommodate their preferences on the right blend of fundamentals and applications.
Các quá trình và thiết bị ứng dụng trong công nghệ sau thu hoạch,Nhiệt động lực học và truyền nhiệt
Keywords: Heat,Heat; Transmission,Industrial applications